FILTERING FEATURES FOR TRACKING OF SPIRALING REENTRY VEHICLES - A. S. Solonar; P. A. Khmarski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The target dynamics model for tracking of spiraling reentry vehicles is considered. The features of Extended Kalman filter modification and Unscented Kalman filter are listed. The estimation performance of Extended Kalman filter modification and Unscented Kalman filter is compared.